PENGUATAN LITERASI MEMBACA KRITIS SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN BERBASIS CERITA KONTEKSTUAL - Devinta Cahyani; Tia Ananda Putri; Keysya Josi Putri Salsabila; Zazqia Putri Anugerah; Mutiara Kartika Sari; Delia Indrawati; Muh Syauqi Malik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical reading literacy is an essential competency for elementary school students in responding to the demands of 21st-century learning. However, reading instruction in elementary classrooms often emphasizes literal comprehension rather than encouraging analytical and reflective thinking skills. This study aims to examine the strengthening of students’ critical reading literacy through contextual story-based learning. The research employed a descriptive qualitative method involving elementary school students as research subjects. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities. The findings indicate that contextual story-based learning increases student engagement, facilitates deeper comprehension of texts, and encourages learners to analyze, interpret, and evaluate reading materials critically. Students demonstrated improved ability to relate textual information to real-life experiences, express opinions, and draw reflective conclusions from stories presented in meaningful contexts. Furthermore, the use of contextual stories created a more interactive learning environment that supported collaborative discussion and active participation. Therefore, contextual story-based learning can be considered an effective instructional strategy for strengthening critical reading literacy among elementary school students and supporting meaningful language learning processes.